DAMPAK KEPUASAN KARYAWAN TERHADAP KEPEMIMPINAN DAN PROMOSI PADA INTENSI UNTUK PINDAH DI PT XYZ - Eriyana, Yana (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
Human resources is one important aspect of a company, instability and uncertainty in terms of human resources or in this research referred to intention to move or high potential turnover may cause a negative impact on company operations and the increasing cost of human resource cost, in the form of training costs already invested in the employee until the cost of recruitment and retraining. High turnover also resulted in the organization is not effective because the company loses experienced employees and the need to retrain new employees.This research aims to analyze how much influence the employee satisfaction of supervision and promotion to intentions to move in PT XYZ. Data used in this research are primary and secondary data. The primary data obtained by interviews and questionnaires, while secondary data from literature study. The analysis method used in this study is multiple regression analysis.The results of this study show that the negative effects and significant correlation between employee satisfaction of supervision and promotion to their intention to move either be partially or together. Keywords: Job satisfaction, Leadership, Promotion, intention to move